Plan de negocios sobre la viabilidad financiera para la creacion de la empresa confecciones en Hermelina Aracataca-Magdalena (2021)
This project was carried out in order to carry out a business plan to know the feasibility of creating a clothing company in Aracataca Magdalena to carry out this project. Marketing and technical studies were carried out, in the same way costs and Financial analyzes were carried out in order to determine the viability of the project as a complement to these, the organizational structure was created to establish the necessary investment, in the same way the environment was taken into account. In what the business plan is developed, the location, competition, advertising and strategies that will be used to promote the final product How the distribution channels, projections and infrastructures that are needed to carry out the production processes of the garments are established, everything to start up the project that generates the expected profits shown in the financial statements.